Evaluasi Kualitas Layanan Website Pusdiklat BPK RI Menggunakan Metode Webqual Modifikasian dan Importance Performance Analysis - Bayu Luhur Wicaksono; Adhi Susanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
This research tries to evaluate the service quality of Pusdiklat BPK RI website from the user’s perception as measured by webqual variables modification approach. This evaluation also focuses on the extent to which perceptions of website service quality perceived by the level of expectation from the perspective of service users Pusdiklat BPK RI website.This research takes an object on a Pusdiklat BPK RI website that addresses in www.pusdiklat.bpk.go.id with 155 respondents were used as sample in measurement the quality of website services. The method used to perform the evaluation through the integration of calculation webqual variables modifications approach within the framework of Structural Equation Modelling (SEM) and Importance Performance Analysis (IPA).This research, shows there is a positive and significant relationship among the variables of website service quality, satisfaction levels, and the intensity of system use.This relation forms the research conceptual model. To improve user satisfaction and user loyalty for services rendered to maintain the consistency of performance some attributes of perceptual interaction and information that has the greatest contribution to the quality of website services. The attributes that are necessary to get attention is the problem of updating information content and response time access to view website. The results are expected can provide feedback to management (team manager) Pusdiklat BPK RI website service in the improvement and development of the website appropriate user expectations.